2021
DOI: 10.1093/texcom/tgab062
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Duration and Lower Quality Sleep Have Widespread Detrimental Effects on Developing Functional Brain Networks in Early Adolescence

Abstract: Sleep is critical for cognitive health, especially during complex developmental periods such as adolescence. However, its effects on maturating brain networks that support cognitive function are only partially understood. We investigated the impact of shorter duration and reduced quality sleep, common stressors during development, on functional network properties in early adolescence—a period of significant neural maturation, using resting-state fMRI from 5566 children (median age = 120.0 months; 52.1% females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 110 publications
1
11
0
Order By: Relevance
“…We first examined how baseline sleep duration influences the 42 baseline behavioral measurements that capture adolescence's problematic behaviors (e.g., conduct and psychosis, 20 items), cognitive functions (e.g., fluid and crystal intelligence, 10 items), and mental health (e.g., depression and anxiety, 12 items). Consistent with some previous findings, we found insufficient sleep had widespread impacts on these baseline behavioral measures (Brooks et al, 2021;Cheng et al, 2020). In particular, we found that 32 out of these 42 assessments showed a significant difference between SS and IS groups after propensity score matching on covariates (Figure 2A; p < .05, FDR corrected).…”
Section: Sleep Duration and Adolescents' Behaviors Cognition And Mental Health Over The Span Of 2 Yearssupporting
confidence: 91%
“…We first examined how baseline sleep duration influences the 42 baseline behavioral measurements that capture adolescence's problematic behaviors (e.g., conduct and psychosis, 20 items), cognitive functions (e.g., fluid and crystal intelligence, 10 items), and mental health (e.g., depression and anxiety, 12 items). Consistent with some previous findings, we found insufficient sleep had widespread impacts on these baseline behavioral measures (Brooks et al, 2021;Cheng et al, 2020). In particular, we found that 32 out of these 42 assessments showed a significant difference between SS and IS groups after propensity score matching on covariates (Figure 2A; p < .05, FDR corrected).…”
Section: Sleep Duration and Adolescents' Behaviors Cognition And Mental Health Over The Span Of 2 Yearssupporting
confidence: 91%
“…Our cohort was selected based on availability and quality of the resting-state fMRI (data release 2.0.1), absence of clinical findings on structural MRI, and no history of bipolar disorder or ADHD, as both disorders that have been associated with aberrant functional connectivity 99 , 100 . The data quality criteria for inclusion are described in detail in 101 , 102 .…”
Section: Methodsmentioning
confidence: 99%
“…The fMRI data processing is described in detail in 101 , 102 . Briefly, neuroimaging data minimally preprocessed by the Data Analysis, Informatics & Resource Center (DAIRC) of the ABCD study 105 were further processed using our group’s Next Generation Neural Data Analysis platform (NGNDA) 106 .…”
Section: Methodsmentioning
confidence: 99%
“…24 Deficits have been attributed to the effect of sleep loss, sleep fragmentation, and/or intermittent hypoxemia on the developing brain circuitry. [25][26][27] The current study focused on attention and executive function because of the potential sensitivity of the frontoparietal attentional network to sleep disruption. However, neither a direct performance measure of attention (GNG) nor a caregiver report of executive function (BRIEF) improved more with adenotonsillectomy.…”
Section: Neurodevelopmental Functioningmentioning
confidence: 99%